Struktur Komunitas Mollusca Bentik Berbasis Kekeruhan Di Perairan Pelabuhan Tanjung Emas Semarang - Hidayat, Jafron Wasiq; Baskoro, Karyadi -; Sopiany, Rini - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2008)
The breakwater of Tanjung Emas Seaport is designed to absorb seawave as well as increase ships stability.Such water stability will trigger the light and small particles to deposite onto the bottom of the water body,eventhough these are easily re-suspended and initiate to create turbidity. Turbididty is one factor affecting Mollusccommunity. In facing the global climate changes, there will be a seriuos problem triggering the turbidity of theseawater and so do the organims. Researh were aimed to study the benthic Mollusc community in different turbiditylevels. Justified ramdom sampling was applied in 14 stations. Community structure of the molluscs were analizeddiscriptively as well as through Shannon-Wiener (H’) and evenness (e) indeces.Result showed that turbidity in PTES varies between 06,750 – 45,250 NTU. Such qualities were relativelyhigh range and can be tolerated by several given species, mainly Gafrarium tumidum, Nuculana acuta and Pyrenesp. These three above species could live within such high turbidity levels, since some of material are part of theirdiets without disturbing their respiration fuction. The highest diversity index H’ was 1,68 and found in Station 5,which is in accordance with its highest turbididyt level 45,250 NTU. The smalest turbidity level occured in Station 8and it was related to smaller diversity index (0,24). There was a tendency, the smaller the turbidity levels the smallerthe diversity indices. Such relatonship was consistence to the other three stations, namely 9,10 and 11. Exceptionwas found in Station 1, where different dominant species occured and diversity index was relatively high. It isbelieved these are related to the presence of warm outlet of Indonesia Power sewage reaching 32,5 centdegree.